ANALISA KEKUATAN SUPER STRUKTUR BUS AKIBAT KECELAKAAN TERGULING (ROLLOVER) DENGAN MENGGUNAKAN UJI PENDULUM - Ahmad Fauzan Suryono (LP2M - Institut Teknologi Padang, 2013)
Rollover accidents are critical issue in many countries in the world because it is one mode that often causing the number of deaths and serious injuries to passengers and crews bus. Therefore, to ensure the safety of passengers necessary to test the strength of the bus superstructure prototype before the bus have road worthy license. Testing is guided by the standards that apply to a state. One of the standards used at many countries in the word is ECE-R66 (Economic Commission for Europe-Regulation 66) which regulates the construction and design of many types of passenger vehicles.In this research, methods of testing are the pendulum test and it was simulated by Finite element software soft ware. The purposes of this study are evaluating compatibility this software, determining energy absorption capacity and the deformation that occurs in the superstructure when a loads subjected from the outside of superstructure. In the pendulum test simulation the maximum deformation value is 520 mm at time is 0.45 s, and 466 mm at time is 1.5 s. The maximum stress occured at the joint between the roof structure with cantrail and it’s value equal to 266 at simulation. Beside it, the simulation show the energy is absorbed by the superstructure at rollover test simulation equal to 66.23%.. Base on simulation result, it can be concluded that the modeling vehicle is indicated safety for passenger if occure rollover accident.